Conducting rapid qualitative research amongst people with experience of rough sleeping in London during the COVID-19 pandemic. Issue 4 (September 2021) - Parkin, Stephen; Neale, Joanne; Roberts, Emmert; Brobbin, Eileen; Bowen, Alice; Hermann, Laura; Dwyer, Georges-Jacques; Turner, Richard; Henderson, Juliet; Kuester, Landon; McDonald, Rebecca; Radcliffe, Polly; et al.
In March 2020, the 'Everyone In' initiative was introduced by the UK government as a public health response to COVID-19. This initiative sought to temporarily accommodate people experiencing rough sleeping in hotels in all local authority areas throughout England. In London, 'Everyone In' involved the procurement of vacant accommodation in over 100 hotels and temporarily re-housed approximately 2000 individuals. A rapid qualitative study was undertaken within two hotels to explore experiences of the initiative from the perspective of people accommodated in the hotels. This article describes how standard qualitative methods were adapted and implemented to complete the study whilst meeting COVID-19 social distancing guidelines. The research involved a longitudinal design of a two-stage qualitative interview that sought to capture residents' experience of 'Everyone In' at two points in time (while in the hotel and when residents had left the hotel). Adapted qualitative methods were employed by a team of 13 researchers. These adaptations included socially distanced leaflet dropping, telephone-based participant recruitment, a remote, multistage, longitudinal qualitative telephone interviewing and rapid framework analysis. 35 hotel residents were recruited into the study (two subsequently withdrew participation). A total of 299 (of a possible 330) short interviews were completed by 33 participants (26 male and 7 female) as part of the multi-stage, longitudinal design of the study. This study indicates that adapted qualitative research methods employed during a pandemic can be successfully applied to obtain insights and experiences (of individuals and groups) otherwise difficult to reach and/or complex to understand.